2022
DOI: 10.3390/ijms232315263
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Ferroptosis Initiating Therapies (FIT) by Targeting the Rewired Lipid Metabolism in Ovarian Cancer Peritoneal Metastases

Abstract: Ovarian cancer is one of the most lethal gynecological cancers worldwide. The poor prognosis of this malignancy is substantially attributed to the inadequate symptomatic biomarkers for early diagnosis and effective remedies to cure the disease against chemoresistance and metastasis. Ovarian cancer metastasis is often relatively passive, and the single clusters of ovarian cancer cells detached from the primary ovarian tumor are transcoelomic spread by the peritoneal fluid throughout the peritoneum cavity and om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 129 publications
0
5
0
1
Order By: Relevance
“…Therefore, protecting cells against elastin-induced ferroptosis can be achieved by silencing LOXs ( Lee et al, 2022 ). Multiple mechanisms exist by which lipid peroxides cause damage to cells, including the generation of ROS through the amplification of lipid peroxidation processes, alterations to the membraneโ€™s physical structure, and lipid peroxidation byproducts ( Zhan et al, 2022 ).…”
Section: Distinctive Features Of Ferroptosismentioning
confidence: 99%
“…Therefore, protecting cells against elastin-induced ferroptosis can be achieved by silencing LOXs ( Lee et al, 2022 ). Multiple mechanisms exist by which lipid peroxides cause damage to cells, including the generation of ROS through the amplification of lipid peroxidation processes, alterations to the membraneโ€™s physical structure, and lipid peroxidation byproducts ( Zhan et al, 2022 ).…”
Section: Distinctive Features Of Ferroptosismentioning
confidence: 99%
“…Several studies investigated the potential of oncometabolites as therapeutic targets in peritoneal cancers by focusing on the metabolic pathways altered in cancer cells [ 92 , 93 , 94 ]. The unique metabolic phenotype of peritoneal cancer cells also presents an opportunity for targeted therapies.…”
Section: Oncometabolites and Precision Cancer Medicinementioning
confidence: 99%
“…Various studies have suggested that aberrant lipid metabolism including cholesterol metabolism positively correlates with metastasis in OC [ 23 , 62 , 63 ]. Fluidity versus membrane rigidity in metastatic cancer cells is governed by the production of lipid rafts packed in the liquid phase order to facilitates a variety of cellular signaling pathways that are interconnected with cancer-related processes [ 53 , 64 ].…”
Section: Cholesterol Metabolism Dysregulation In Cancermentioning
confidence: 99%